2020
DOI: 10.1038/s41598-019-57307-9
|View full text |Cite
|
Sign up to set email alerts
|

The response of glyphosate-resistant and glyphosate-susceptible biotypes of Echinochloa colona to carbon dioxide, soil moisture and glyphosate

Abstract: physiological and growth responses of two Australian Echinochloa colona biotypes (glyphosateresistant and susceptible, produced from a single population) to different concentrations of carbon dioxide (co 2) (ambient ~450 ppm and elevated ~750 ppm) and soil moisture (well-watered and waterstressed) were analyzed. Elevated CO 2 and well-watered conditions resulted in E. colona plants with greater biomass, height and numbers of tillers and leaves in both biotypes; however, no significant response was observed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…The current study revealed that the application of the recommended label rate of glyphosate reduced dry weight of the resistant E. colona accessions (ET2 and ET4) only by 18%-22%, as compared to the untreated control. Such findings are in accordance with the corresponding of Mollaee et al [22] who noticed that the application of the recommended rate of glyphosate reduced the dry weight of a resistant E. colona by 25% under conditions of increased soil moisture, whereas this accession under water stress conditions was completely unaffected. The susceptible accession studied during this experiment was controlled by 72%, 88%, and 97% when treated with 1/2X, X and 2X rates of glyphosate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study revealed that the application of the recommended label rate of glyphosate reduced dry weight of the resistant E. colona accessions (ET2 and ET4) only by 18%-22%, as compared to the untreated control. Such findings are in accordance with the corresponding of Mollaee et al [22] who noticed that the application of the recommended rate of glyphosate reduced the dry weight of a resistant E. colona by 25% under conditions of increased soil moisture, whereas this accession under water stress conditions was completely unaffected. The susceptible accession studied during this experiment was controlled by 72%, 88%, and 97% when treated with 1/2X, X and 2X rates of glyphosate.…”
Section: Discussionsupporting
confidence: 92%
“…Soil moisture conditions as well as temperature are also key factors affecting the efficacy of glyphosate against Echinochloa spp. In particular, Mollaee et al [22] noted that when treated with 1440 g a. e. ha −1 of glyphosate, the resistant population survival was recorded at 19% under increased soil moisture conditions, whereas this value was by 43% higher under water-stress conditions. Increased GR 50 values, resistance indices, and survival percentage were observed at 30 • C in glyphosate-resistant E. colona populations during both the experiments of Nguyen et al [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in 2015. The glyphosate-resistant biotype was confirmed to be resistant in a screenhouse study, in which plants were sprayed with different doses of glyphosate [34]. According to an experiment conducted by Mutii et al (2019) at the Gatton research field, the glyphosate-resistant and susceptible biotypes were propagated by the cloning method that produces individual plants with the same genetic background as their parents [35].…”
Section: Seed Description and Seedling Preparationmentioning
confidence: 99%
“…Reduced soil moisture content resulted in a decrease in the efficacy of glyphosate [12,40]. In our previous study, we observed that in the water stressed condition, glyphosate efficacy was decreased in both biotypes [34]. This response could be caused by less absorption and translocation of glyphosate as the herbicide is mainly translocated by vascular transportation [41].…”
Section: Plos Onementioning
confidence: 99%